COMMUNICATION SYSTEMS FOR HIGH SPEED FLYING DEVICES WITH REPETITION CODES - Dwi Juniarto; Khoirul Anwar; Dharu Arseno (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2020)
Communication systems for devices moving at high speed are suffering from error-floor due to the Doppler effect. This paper proposes a simple narrowband communication systems for high speed flying devices for critical applications such as missile and drone. To make the system simple, we consider Repetition codes and slight increase of the number of pilot symbols such that the system can predict accurately the fast-changing channel due to time-selective fading. The equalizer in this paper is designed according to the addition of the pilot symbols so that the system works at a maximum speed of 450 km/h to make successful operation for missile and drone before they are taken down by the enemy. Computer simulations are used to evaluate the performance of the proposed communication systems. The operating frequency is industrial, scientific, and medical (ISM) band, where binary phase shift keying (BPSK) modulations are used with Repetition codes being the channel coding. The bit error rate (BER) performance is evaluated under additive white Gaussian noise (AWGN) and Rayleigh fading channels. The results confirm that excellent BER performances are obtained having error-floor less than 10-4 making many applications, including image transmission, are possible, which are great for high speed flying devices even with Repetition codes and simple zero forcing (ZF) equalizer. The results of this study are expected to help the development of future communication systems for missile, drone, and airplane applications.